Estimasi Sumberdaya Bijih Besi Menggunakan Metode Ordinary Krigging di PT. Gamindra Mitra Kesuma, Kec. Sungai Beremas, Kab. Pasaman Barat, Sumatera Barat - Rido Muhammad Afif; Adree Octova (Journals Mining Engineering : Bina Tambang, 2019)
PT.Gamindra Mitra Kesuma is a mining company currently exploring iron ore in the district. Sungai Beremass to get the distribution of iron ore and the amount of iron ore available in the area. Exploration is carried out by drilling a total of 11 drill hole points on an area of 20 hectares. To find out the amount and distribution of iron ore, it is necessary to estimate the resources which currently researchers use the ordinary krigging method with spatial estimation where the error variance is minimized. Researchers used a 3-dimensional block model with a block size of 30m x 30m x 1m which is in the estimation of the study area. To carry out the process of estimating krigging, the value of sill, range, nugget is needed, to facilitate the fitting of the variogram. By analyzing the variogram with 4 main directions and all directions will get the data distribution. Estimation results using the ordinary krigging method in the form of block models that have been topped by topography and bottom topography. The estimation is obtained in the number of blocks from the results of the top topography and bottom topography where the total iron ore tonnage is 31.680.000 tons and overburden is 12.736.800 bcm with a stripping ratio of 0.402 bcm / ton. Keywords : Resource, Estimation, Ordinary Kriging, Variogram, Iron Ore